Pentylenetetrazol-induced seizures strength in diabetic and normal serum glucose elevated male mice - Khalili, Mohsen; Kiasalari, Zahra; Abdullahi, Payman Raise (International Journal of Scientific Reports, 2016)
Background: Epilepsy is one of the most important neurological disorders, afflicting both genders during their lifetime. Metabolic disturbances, including hyperglycemia and hypoglycemia, are one of the main reasons of seizures in which frequently have been seen in diabetes mellitus. A large body of literature has investigated correlation between hyperglycemia, hypoglycemia and seizure. However, a definitive conclusion has not been taken, yet. Hence, we developed a rodent model of PTZ-induced seizure in order to investigate about relation between PTZ-induced seizures and glycemic changes, including diabetic and non-diabetic hyperglycemia and hypoglycemia. Methods: We chose 50 naive, adult male inbred mice of the Balb/c strain (aged 8–10 weeks, weighted 25-35 grams) and divided them into 5 groups, randomly (n=10 in each groups): 1. Control (received saline and citrate buffer). 2. Diabetic group (received STZ 140 mg/kg I.P). 3. Diabetic+Glibenclamide group (received STZ 140 mg/kg I.P and treated with Glibenclamide 1 mg/kg I.P daily). 4. Non-diabetic hyperglycemic group (received glucose "D-dextrose" 2 g/kg I.P 30 min before PTZ administration. 5. Hypoglycemic group (the animals were fasted one day other days during experimental period). Chemical kindling was induced by PTZ injection (35 mg/kg, I.P), every other days (11 periods that lasted 22 days). Results: Our data shown non-diabetic hyperglycemic mice that had elevated blood glucose levels, were more resistant to seizures compared to control group (p<0.05). Threshold and duration of the second phase of the seizures in non-diabetic hyperglycemic mice were increased (p<0.001). Moreover, threshold of the phase 5 was enhanced (p<0.001). Again, hypoglycemic mice had statistically significant decrease in threshold of phase 5 compared to control group (p<0.05). Conclusions: We found that acute non-diabetic hyperglycemia not only have had no aggravating effects on seizure susceptibility but also have shown anticonvulsive effects. As well, we found that hypoglycemia has decreased threshold of phase 5 in challenge dose, i.e. onset of the most severe phase of the seizures was accelerated.